2007
DOI: 10.1177/0731684407079426
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Polymer Consolidated Composites

Abstract: Polymer matrix composites (PMCs) are used extensively in industry, varying from high performance structural composites used in the aerospace industry, to products such as insulation boards used in the construction industry. At either end of this spectrum, the matrix could be regarded to have a different functionality. In high performance composites, the polymer forms a continuous phase around the reinforcement, whereas, in products such as particle boards, the matrix may no longer be continuous. Therefore, PMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…This is in good agreement with Boeing et al who reported that excess monomer results in shrinkage of exothermic temperatures which are untenable. It is also reported that, there is an optimum content of monomer beyond which important properties of the cured product values decrease rapidly . Depending on these results, the ratio 60:40 wt% was kept constant throughout this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in good agreement with Boeing et al who reported that excess monomer results in shrinkage of exothermic temperatures which are untenable. It is also reported that, there is an optimum content of monomer beyond which important properties of the cured product values decrease rapidly . Depending on these results, the ratio 60:40 wt% was kept constant throughout this study.…”
Section: Resultsmentioning
confidence: 99%
“…Particle characteristics such as particle size, size distribution, and geometric arrangement of the fillers in the polymer matrix, density, and porosity influence the mechanical properties of polymeric composites . The effect of thermally or chemically treated kaolin on the compressive strength values of the polymeric composites are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The particulates are mainly cellulosic materials, e.g., wood flour, wheat stalk, sugar cane bagasse, and cornhusks . The adhesives/binders used for such composites are mainly thermosetting resins that include urea‐formaldehyde, phenol formaldehyde, melamine formaldehyde, and diphenyl diisocyanate . However, use of such thermosets possess a risk of potential harmful formaldehyde emissions, limited recyclability and processing …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The adhesives/binders used for such composites are mainly thermosetting resins that include urea-formaldehyde, phenol formaldehyde, melamine formaldehyde, and diphenyl diisocyanate. 13 However, use of such thermosets possess a risk of potential harmful formaldehyde emissions, limited recyclability and processing. 13 Other bio-particulates of non-cellulosic origin such as egg shells, chicken feathers, sea weed, and waste shell fish have been incorporated as fillers into synthetic polymers at fractions usually <30 wt %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation